1998
DOI: 10.1006/brcg.1998.1007
|View full text |Cite
|
Sign up to set email alerts
|

A Search for the Optimal Stimulus

Abstract: How do stimulus size and item number relate to the magnitude and direction of error on center estimation and line cancellation tests? How might this relationship inform theories concerning spatial neglect? These questions were addressed by testing twenty patients with right hemisphere lesions, eleven with left hemisphere lesions and eleven normal control subjects on multiple versions of center estimation and line cancellation tests. Patients who made large errors on these tests also demonstrated an optimal or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
32
0

Year Published

1998
1998
2017
2017

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(36 citation statements)
references
References 32 publications
(49 reference statements)
3
32
0
Order By: Relevance
“…Patient 2 showed that magnitude estimation is biased following damage to temporo-parietal regions of the left hemisphere even in the absence of behavioral symptoms of neglect. Her data are consistent with previous studies of magnitude estimation in patients without neglect following right hemisphere injury (MacKay, 1963;Mennemeier et al, 1998;Mennemeier et al, 2002;Mennemeier et al, 2005). Patient 2 had an expressive aphasia but we do not think deficits in comprehension or writing account for bias in magnitude estimation because her data fit power functions, indicating response consistency, and her r 2 values were not appreciably lower than either patient 1 or patients with right hemisphere injury who do not have aphasia.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Patient 2 showed that magnitude estimation is biased following damage to temporo-parietal regions of the left hemisphere even in the absence of behavioral symptoms of neglect. Her data are consistent with previous studies of magnitude estimation in patients without neglect following right hemisphere injury (MacKay, 1963;Mennemeier et al, 1998;Mennemeier et al, 2002;Mennemeier et al, 2005). Patient 2 had an expressive aphasia but we do not think deficits in comprehension or writing account for bias in magnitude estimation because her data fit power functions, indicating response consistency, and her r 2 values were not appreciably lower than either patient 1 or patients with right hemisphere injury who do not have aphasia.…”
Section: Discussionsupporting
confidence: 89%
“…Power function relationships are altered by right hemisphere injury, particularly in association with unilateral neglect (Chatterjee, Mennemeier, & Heilman, 1992b;Chatterjee, Dajani, & Gage, 1994;Chatterjee, Mennemeier, & Heilman, 1994;Chatterjee, 1995;Mennemeier, Rapcsak, Dillon, & Vezey, 1998;Mennemeier, Vezey, Lamar, & Jewell, 2002;Mennemeier et al, 2005) which follows damage to a neural system involving frontal, cingulate, temporal, and parietal cortices in both hemispheres (Heilman, Watson, & Valenstein, 1994;Mesulam, 1981;Vallar & Perani, 1987;Karnath, Ferber, & Himmelbach, 2001;Karnath, Himmelbach, & Rorden, 2002). When data from bedside tests for neglect are fit to power functions, a restricted range of perception is revealed in neglect patients signaled by a decrease in the power function exponent (a flatter slope) and an increase in the constant (an elevated y-intercept) relative to normal subjects (Chatterjee et al, 1992b;Chatterjee, Mennemeier, & Heilman, 1992a;Chatterjee, 1995;Mennemeier et al, 2002;Mennemeier et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Accuracy varies with line length-short lines being overestimated and long lines underestimated. The point of crossover is also a point at which bisections are most accurate and, as a result, least consistently bisected to one side of true center (Mennemeier, Rapcsak, Dillon, et al, 1998). Replicating previous experiments (Mennemeier, Rapcsak, Pierce, et al, 2001;Mennemeier, Rapcsak, Dillon, et al, 1998), normal subjects in this study were least accurate when bisecting the shortest lines and the direction of errors on short lines was very consistent.…”
Section: Discussionsupporting
confidence: 82%
“…Crossover, Orientation Bias, and Magnitude Estimation-Crossover has been observed on line bisection and length estimation tasks in both young and old normal subjects (Mennemeier, Vezey, Lamar, et al, 2002;Mennemeier, Rapcsak, Pierce, & Vezey, 2001;McCourt & Jewell, 1999;Mennemeier, Rapcsak, Dillon, & Vezey, 1998;Manning, Halligan, & Marshall, 1990). Crossover also occurs in patients without neglect following right or left brain injury (Mennemeier, Vezey, Lamar, et al, 2002;Mennemeier, Rapcsak, Pierce, et al, 2001;Mennemeier, Rapcsak, Dillon, et al, 1998).…”
Section: Introduction Overviewmentioning
confidence: 99%
See 1 more Smart Citation